Biomathematics : modelling and simulation - Misra, J. C. (World Scientific, 2006)
This book on modelling and simulation in biomathematics will be invaluable to researchers who are interested in the emerging areas of the field. Graduate students in related areas as well as lecturers will also find it beneficial. Some of the chapters have been written by distinguished experts in the field. Sample Chapter(s). Chapter 1: Detecting Mosaic Structures in DNA Sequence Alignments (1,349 KB). Contents: Detecting Mosaic Structures in DNA Sequence Alignments (D Husmeier); Application of Statistical Methodology and Model Design to Socio-Behaviour of HIV Transmission (J Oluwoye); A Stoch.